2017
DOI: 10.1002/net.21751
|View full text |Cite
|
Sign up to set email alerts
|

Quadratic unconstrained binary optimization problem preprocessing: Theory and empirical analysis

Abstract: Abstract. The Quadratic Unconstrained Binary Optimization problem (QUBO) has become a unifying model for representing a wide range of combinatorial optimization problems, and for linking a variety of disciplines that face these problems. A new class of quantum annealing computer that maps QUBO onto a physical qubit network structure with specific size and edge density restrictions is generating a growing interest in ways to transform the underlying QUBO structure into an equivalent graph having fewer nodes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 17 publications
0
42
1
3
Order By: Relevance
“…The data points represent average percent reductions for 16 problems, hence for the 1% edge dense 10000 variable problems about 600 variables were determined in the first pass (6%) and 2500 on average were determined in the second pass. In comparison to our earlier work (Lewis & Glover, 2016) using only 3 basic rules (R1, R2 and R3.4) embedded in a procedure called QPro, we find here that the additional rules yield about a 22% improvement in reduction overall and positively affect every problem. Most importantly the additional rules yield ten 100% reductions in contrast to 0 reductions using only rules 1, 2 and 3.4.…”
Section: Test Results Using Cplex and Qpro+contrasting
confidence: 60%
“…The data points represent average percent reductions for 16 problems, hence for the 1% edge dense 10000 variable problems about 600 variables were determined in the first pass (6%) and 2500 on average were determined in the second pass. In comparison to our earlier work (Lewis & Glover, 2016) using only 3 basic rules (R1, R2 and R3.4) embedded in a procedure called QPro, we find here that the additional rules yield about a 22% improvement in reduction overall and positively affect every problem. Most importantly the additional rules yield ten 100% reductions in contrast to 0 reductions using only rules 1, 2 and 3.4.…”
Section: Test Results Using Cplex and Qpro+contrasting
confidence: 60%
“…11 show that tens of microseconds suffice to achieve a low enough (below 10 −3 ) FER to support high throughput communication for 60-user BPSK, 18-user QPSK, or four-user 16-QAM suffices to serve four users with the idealized median performance of Opt. QuAMax (mean Fix) achieves a similar performance with slightly smaller numbers of 8 Outlier mitigation methods for QA may address such outliers in future work [40]. users.…”
Section: Quamaxmentioning
confidence: 88%
“…In terms of classical approach, Boros et al presented a set of local search heuristics for Quadratic Unconstrained Binary Optimization (QUBO) problems, providing indicative simulation results on various benchmark tests [30]. The reduction of the large matrix size in QUBO was the main topic in [25] by Lewis and Glover. Glover et al showed in a step by step procedure how one can translate a problem with particular characteristics into a QUBO instance [29].…”
Section: Related Workmentioning
confidence: 99%
“…At this point, it is important to pause and confirm that the constraints in Equations (25) and (26) conform to the QUBO formulation requirements, in the sense that, after the expansion of the square, we get a sum of terms, where each term is the product of input data such as c u,v or l v and at most two binary decision variables.…”
Section: Example 1 To See the Form Of Equationsmentioning
confidence: 99%
See 1 more Smart Citation